Tinjauan Pola Bentuk Pada Ruang Okupasi Di Klinik Tumbuh Kembang My Super Kidz - Adli, Raedi Nur (Fakultas Desain Universitas Komputer Indonesia, 2022)
Occupational therapy is one type of therapy that is specifically applied to someone who has special health problems, so that they can return to normal activities. Occupational therapy is one of the effective methods for children to be able to find out what learning methods are suitable for them. With occupational therapy, parents have hope that their children can carry out daily activities independently. This method usually involves the game and the surrounding facilities as a tool. One thing to note is the selection of shape patterns. The pattern of forms applied to the therapy room has a role in the child's therapy process. These patterns can be in the form of games, furniture facilities or treatment of floors or walls. The purpose of this study was to find out the concept of the shape pattern applied to the occupational therapy room at the my super kidz child development clinic and its benefits for children.